Pendekatan Organizational Behaviour dalam Peningkatan Motivasi Kerja Guru di MAN Kota Lhokseumawe - Alhuda, Alhuda (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) IAIN Lhokseumawe, 2024)
This study focuses on the management of teacher work motivation at MAN Kota Lhokseumawe, emphasizing the application of Organizational Behaviour (OB) approach. The aim of this research is to understand how the OB approach can enhance teacher motivation and performance within the educational context of this madrasah. This research employs a qualitative method with a case study approach. Data collection techniques include in-depth interviews with the Head of MAN Kota Lhokseumawe and several teachers, participatory observation within the school environment, and document analysis related to policies and motivation programs. Data analysis procedures involve data reduction, presentation of data in narrative form, and verification through triangulation to ensure consistency and validity of the findings. The results indicate that the application of the OB approach at MAN Kota Lhokseumawe has successfully improved teacher motivation. The implemented motivation management strategies include providing rewards, professional development, and active participation in decision-making. Supporting factors such as human resources competence, facilities and infrastructure, and strategic location contribute to teacher motivation. However, there are several challenges, such as teachers' distant domiciles and sectoral egos in teamwork, which affect the effectiveness of motivation management. Practical implications of this study include the need for flexible policies to support teachers living far away, strengthening team collaboration, and providing training focused on communication skills and conflict management.